EXPERIENCES OF LEGAL INTEGRATION AND RECEPTION BY THE BRICS COUNTRIES: FIVE PASSENGERS IN A BOAT (WITHOUT A DOG) - M. Zakharova; V. Przhilenskiy (BRICS Law Journal)
This article assesses the problems and prospects of the development of cooperation among the BRICS countries’ in the sphere of law and the movement of these countries towards the creation of a common legal framework. The article presents a comparative analysis of the systems of law, including the cultural, historical, social and political contexts of their formation and development as well as the functioning of the systems in the conditions of the modern world.The article particularly focuses on the subject of a common philosophy of law for the BRICS countries that would allow not only to establish the interaction of such dissimilar partners in the legal sphere, but also to move towards a new model of legal interaction for the whole world that has embarked on the path of globalization. Special means allowing the assessment of the possibility of future legal integration and globalization based on a common philosophy of law are the traditions and values of the civilizations represented by the BRICS countries. The article suggests that the core of the civilizational and value- based identity of each BRICS partner consists in a set of ideas and interpretations of the notion of justice clearly manifested in the controversy with the theory and ideology of justice proposed by the initiators and leaders of globalization - the countries of the West led by the United States. The theory and ideology of justice promoted by the "Atlantists" is concisely formulated in the book "A Theory of Justice" by John Rawls. Therefore, the reaction to and discussion of such a theory by the philosophers and jurists from Russia, India and China allows determining the contours of the common philosophical and legal position of these countries as well as outlining its significance for the future of the BRICS countries and, perhaps, of the whole system of legal relations in a new globalizing world.